Vulnerabilities and risk mitigation in Indonesia’s halal poultry chain: Bridging compliance and practice - Puji Handayani Kasih; Keny Rahmawati; Ismianti Ismianti; Astrid Wahyu Adventri Wibowo; Hasan Mastrisiswadi (OPSI)
Halal risk mitigation in certified poultry processing is the focus of this study.  The primary objectives are to map the important risk points in the halal poultry supply chain, understand how certification criteria are applied, and evaluate how stakeholder awareness and behaviour affect halal compliance. This research applied a descriptive qualitative approach, leveraging the case study technique through interviews with major stakeholders in the chicken meat supply chain. This research uses source triangulation techniques to validate the data by comparing information from interviews and literature reviews. The findings reveal several critical issues in the halal poultry supply chain, including limited control over halal inputs such as feed and vaccines, and low awareness among farmers regarding halal standards. Inadequate transaction documentation and the unclear halal status of chickens during transfer further compromise compliance. The slaughtering process often does not adhere to shariah requirements, with poor separation between clean and dirty areas, increasing the risk of cross-contamination. Additional concerns include contamination during transportation due to the use of non-designated or unhygienic vehicles, and the absence of halal labelling alongside the use of ingredients from unverified sources.